Understanding the challenges of healthcare transition in the context of HIV-related stigma for young adults with perinatal HIV in Thailand - Linda Aurpibul; Chutima Saisaengjan; Wipaporn Natalie Songtaweesin; Supunnee Masurin; Tulathip Suwanlerk; Thanyawee Puthanakit (PLoS ONE, 2025)
The healthcare transition during adolescence and young adulthood has consistently been reported as a critical period for attrition and adverse health outcomes. The study assessed HIV-related stigma and transition experiences among young people living with perinatal HIV (YPHIV) in Thailand. We conducted a mixed-methods cross-sectional study at two research sites in Chiang Mai and Bangkok, Thailand from December 2023 to February 2024. We recruited YPHIV aged between 18–30 years who remained under care in pediatric HIV clinics (group A), those who had transitioned to adult care from those clinics (group B), and caregivers of group B participants (group C). We assessed HIV-related stigma using the validated 8-item Thai Internalized HIV-related Stigma Scale brief (Thai-IHSS brief) and transition-related experiences through in-depth interviews and focus group discussions. Thirty YPHIV (median age 23 years [IQR 22–26]) and ten caregivers were enrolled. The Thai IHSS brief score revealed a low level of internalized stigma in the study participants (median score 14; IQR 11–17). Anticipated negative thoughts and negative self-thoughts were common. HIV-related stigma experiences of YPHIV and caregivers were grouped into 3 themes: internalized, anticipated, and enacted stigma/discrimination. Transition experiences of YPHIV in both groups included hesitation to navigate care in adult clinics and feeling unprepared, perceived loss of support, and demotivation from being in care. Anticipated stigma and social problems were expressed by YPHIV and caregivers. In the focus groups, YPHIV indicated their need to learn about the transition beforehand, to be guided to the new clinic while staying connected to their original clinics, and to extend time in the pediatric clinic until they were more confident with transitioning care. In conclusion, we found many stigma issues started since childhood, plus collective experience while growing up. The internalized HIV-related stigma influenced the healthcare transition journey of YPHIV. Healthcare providers need additional guidance on how to manage transition in YPHIV, including individualized transition plans for those at increased risk of adverse outcomes, interventions to manage internalized stigma, and follow-up strategies after transition.